The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.2196/18982
|View full text |Cite
|
Sign up to set email alerts
|

Adaptation and Evaluation of a Symptom-Monitoring Digital Health Intervention for Patients With Relapsed and Refractory Multiple Myeloma: Pilot Mixed-Methods Implementation Study

Abstract: Background Relapsed and refractory multiple myeloma (RRMM) is a bone marrow cancer that requires systemic treatment, which often results in severe symptom burden. Recent studies have found that electronic patient-reported outcome (ePRO) interventions implemented in the clinic setting have had positive outcomes for other oncology populations. Evidence of the efficacy of a similar approach is lacking for patients with RRMM. Objective Recent recommendation… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
47
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(47 citation statements)
references
References 36 publications
0
47
0
Order By: Relevance
“…The 91 studies included for analysis describe 73 mHealth apps, of which 29 (40%) were designed for supporting any cancer types [ 9 , 12 , 47 , 48 , 50 , 54 , 56 - 58 , 65 - 69 , 71 , 73 , 74 , 76 , 81 - 83 , 85 - 88 ,​ 90 , 91 , 93 , 105 - 109 , 111 - 113 , 116 , 117 , 121 , 122 , 125 , 128 ], followed by 17 (23%) on breast cancer [ 49 , 64 , 70 , 72 , 77 ,​ 78 , 80 , 95 - 98 , 103 , 114 , 115 , 118 , 124 , 126 , 129 - 131 ], 5 (7%) [ 52 , 53 , 63 , 99 , 101 , 102 ] on gastric and colon cancer types, 3 (4%) [ 75 , 79 , 89 , 119 ] on lung cancer, 3 (4%) on thyroid cancer [ 84 , 100 , 123 ] type, and 2 (3%) on hematological cancer types [ 9 , 55 , 56 ,…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The 91 studies included for analysis describe 73 mHealth apps, of which 29 (40%) were designed for supporting any cancer types [ 9 , 12 , 47 , 48 , 50 , 54 , 56 - 58 , 65 - 69 , 71 , 73 , 74 , 76 , 81 - 83 , 85 - 88 ,​ 90 , 91 , 93 , 105 - 109 , 111 - 113 , 116 , 117 , 121 , 122 , 125 , 128 ], followed by 17 (23%) on breast cancer [ 49 , 64 , 70 , 72 , 77 ,​ 78 , 80 , 95 - 98 , 103 , 114 , 115 , 118 , 124 , 126 , 129 - 131 ], 5 (7%) [ 52 , 53 , 63 , 99 , 101 , 102 ] on gastric and colon cancer types, 3 (4%) [ 75 , 79 , 89 , 119 ] on lung cancer, 3 (4%) on thyroid cancer [ 84 , 100 , 123 ] type, and 2 (3%) on hematological cancer types [ 9 , 55 , 56 ,…”
Section: Resultsmentioning
confidence: 99%
“…Regarding the intervention source, the literature reported that participating in the development phase increased the likelihood of later embracing the technology. Most analyzed apps have been developed collaboratively [8,53,[55][56][57][58]62,72,73,75,77,87,101,103,104,107,109,114,[116][117][118]122,127,131], often including HCPs, potential patients, and external technology partners responsible for actual software development [56,66,71,78,89,97,105,125,127,129,130]. For instance, the development of eOncoSalud was carefully planned during a series of 7 nominal consensus meetings involving a wide range of stakeholders [56].…”
Section: Intervention Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…One small study of 11 patients with relapsed or refractory MM examined the value of patientreported symptoms after one to three prior lines of therapy. 41 Patients were asked to report symptom presence, severity, and interference via the National Cancer Institute's Patient-Reported Outcomes version of the Common Terminology Criteria for Adverse Events (PRO-CTCAE) weekly or, if desired, spontaneously via cell phone app or web portal. At predefined thresholds, patients received guidance and HCPs were alerted.…”
Section: Patient-reported Symptom Monitoringmentioning
confidence: 99%
“… 5 , 6 Digital health technology applications may bridge the gap between academic lengthy PRO questionnaires and real-time monitoring of HRQoL. Current strategies on integrating digital health technology applications in the care of MM patients include digital health coaching and actigraphy during autologous stem cell transplantation, 7 , 8 artificial intelligence-based symptom monitoring, 9 and medication adherence when transitioning subcutaneous treatments to oral-based treatments. 10 To our knowledge, actigraphy has not yet been studied to evaluate physical activity trends in newly diagnosed symptomatic MM patients receiving induction chemotherapy as it correlates with HRQoL.…”
Section: Introductionmentioning
confidence: 99%